Effective labour delivery room space configuration for Malaysian hospitals - Mohd Nawawi, Norwina; Zen, Ismawi; Khalid, Aisyah (2010)
The planning and design of Labour Delivery Room (LDR) in the Malaysian hospitals ranged from simple utilitarian spaces of public hospitals to a 4-5 star spaces in private facilities. Although the area may differ from one design to another in conforming to certain acceptable standards or norms, the space configuration of these rooms remained an enigma to its effectiveness and the grid system chosen to fit in the repetitive module. The study is therefore conducted on selected hospitals with the LDR, and of various space configurations, so as to obtain the critical dimension required to perform safe normal delivery effectively. As a qualitative research, the data will be obtained through literature review, planned and unplanned observation, structured and random interview as well as re-measurement of the rooms/spaces as bases of measurement. The significance of the finding was to ascertain the critical dimension required to perform the main function of the space as labour and delivery area apart from other findings of importance for the well being of the users.